Understanding Moslem Friendly Tourism in the Lombok Island: A Halal Tourism Literacy Role - Didy Ika Supryadi; Lalu Edy Herman Mulyono; Santi Nururly; Himawan Sutanto; Taufan Handika Putra (Petra International Journal of Business Studies, 2025)
This study aims to examine the impact of information overload on the purchase behavior of millennials residing in Java. This study aims to identify the contribution of halal tourism literacy based on self-efficacy theory to visit decisions by integrating push and pull motivation theory as a bridge. Based on this theoretical framework, this study aims to analyze the relationship between halal tourism literacy, internal motivation, and external motivation in encouraging visit decisions. This research was conducted using primary data, namely by distributing questionnaires online via Google Forms and disseminating them through social media, namely Instagram, Line, and WhatsApp. The sampling technique used was purposive sampling, with a sample size of 150 respondents. Data processing uses Partial Least Squares (Smart-PLS) version 3.2.9. This study found that halal tourism literacy does not directly influence the decision to visit, but halal tourism literacy indirectly influences the decision to visit through internal motivation. Similarly, external motivation can mediate the relationship between halal tourism literacy and the decision to visit. This study contributes to resolving the controversy in previous research regarding the influence of halal tourism literacy on travel decisions. This study adds to the existing literature. Instead of relying solely on Halal Tourism Literacy, this study integrates Push and Pull Motivation Theory as a mediating framework, showing that internal and external motivations play a key role in driving the decision to visit Lombok Island. This study offers a more comprehensive, empirical approach, providing valuable insights for tourism stakeholders to focus on Halal compliance and the motivating factors that enhance the appeal of Muslim-friendly destinations.